The Quizizz Application is an Arabic Online Learning Evaluation Tool at The University Level - Miatin Rachmawati; Ahmad Rizki Nugrahawan; Nurul Hidayati Rofi’ah (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2022)
The purpose of this study was to show how to use Quizizz-based psycholinguistic evaluation in a learning evaluation and to assess its effectiveness. This study used a qualitative descriptive case study approach, which resulted in descriptive data in the form of written or spoken statements from the participants and observations of their behavior. Thus, direct interviews with students of Independent Campus Freedom To Learn are one of the data collection strategies. According to the findings of the questionnaire and interview distribution, 89 percent of respondents claimed that this evaluation was not dull but provided a lot of diversity, even if 14.3 percent said they utilized Quizizz because it didn't support the signal. Furthermore, 100% of respondents thought the learning evaluation method was not dull or monotonous. These findings suggest that Quizizz-based evaluation is a lot of fun and doesn't get boring in the classroom, and it gets students excited about learning.